Answer:
Step-by-step explanation:
<u>Given recursive formula:</u>
- a₁ = -1
- aₙ = - 3aₙ₋₁ + 6 for n ≥ 2
<u>The first 4 terms are:</u>
- a₁ = - 1, given
- a₂ = - 3*(-1) + 6 = 3 + 6 = 9
- a₃ = - 3*(9) + 6 = - 27 + 6 = - 21
- a₄ = - 3*(-21) + 6 = 63 + 6 = 69
8 for 6 is the answer I think
Standard form : Ax + By = C
y - 4 = 0
y = 4...this is a horizontal line and a horizontal line has a 0 slope
so in standard form, ur equation is : 0x + y = 4
Answer:
3k+3
Step-by-step explanation:
Answer:
what exactly did u want me to work out?